MODEL MITIGASI BENCANA BANJIR DENGAN MENGGUNAKAN PENDEKATAN TERINTEGRASI UNTUK KETAHANAN KOMUNITAS DI KABUPATEN PANGKEP - Rusdi, Rusdi; Padli, Feri; Ibrahim, Ibrahim; Jamal, Nur Fitri; Syahrudin, Darma Jaya (Social Landscape Journal, 2024)
This research aims to: 1) Find out the causes of flooding in Pangkajene District, Kab. Pangkep. 2) Knowing the impact of the flood disaster on the people of Pangkajene District, Kab. Pangkep. 3) Know how to mitigate flood disasters for the people of Pangkajene District, Kab. Pangkep. The type of research used in this research is descriptive qualitative. The data collection techniques are through observation, interviews and documentation. The results of this research show that 1) the cause of the flood disaster in Pangkajene District, Kab. Pangkep is high rainfall, poor drainage 2) The impact of flooding on the community: physical impact, economic impact and social impact 3) Mitigation carried out by the community before the flood occurs, namely, the community has been advised by the local village that there will be a flood. Mitigation when a flood occurs, namely the community is provided with refugee camps, the Government and NGOs ensure that there are no casualties and the community takes steps to prevent water such as filling sand in sacks, the community receives food distribution, Mitigation after a flood disaster, namely the community cleans their houses and repairs to roads and gutters by the government gradually.